Stability determination method for DC micro-grid in master-slave control mode - PENG YONGGANG; HU HUIYONG; WEI WEI (2017)
The invention relates to the stability analysis technology in the DC micro-grid technologies, and aims to provide a stability determination method for a DC micro-grid in the master-slave control mode. The method comprises the following steps: using the unit connection method to carry on the Thevenin/Norton equivalent to the power modules of each power supply and each constant power load so as to obtain the corresponding impedance/admittance, and obtaining the impedance matrix of the main power supply, the admittance matrixes of the slave power source and the constant power load; according to the known resistive load size of each node, obtaining the resistive load admittance matrix, and obtaining the system node admittance matrix according to the inter-node cable parameter; placing each matrix into the stability criterion and calculating its pole; if all the poles are on the left half plane, determining that the system is stable; and if there is a pole on the right half plane, determining the system is unstabl